Mapping and testing product-level vulnerabilities in granular production networks - Berthou, Antoine (OECD Science, Technology and Industry Working Papers, 2024)
This paper conducts an in-depth mapping of global value chain (GVC) vulnerabilities, using granular product-level trade data to identify vulnerable products with limited suppliers and substitutability. The study reveals that, in OECD countries, approximately 8% of foreign-sourced intermediate products are vulnerable, with about 50 products identified as highly vulnerable, particularly in the pharmaceutical, mining, and manufacturing sectors. The paper also introduces a quantitative framework for simulating supply shock transmission from upstream suppliers to downstream industries over the short and medium term. This framework leverages unique data that combine Inter-Country Input-Output with detailed product-level trade data from Comtrade. Through simulation exercises, the paper highlights the role of supplier concentration and geography in shock transmissions, as well as the effectiveness of policies in mitigating these impacts. This novel cross-country assessment of GVC disruptions provides new insights on how to manage supply chains in a global economy subject to multiple risks